2015
DOI: 10.4012/dmj.2014-167
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity evaluation of luting resin cements on bovine dental pulp-derived cells (bDPCs) by real-time cell analysis

Abstract: To evaluate the cytotoxicity of resin cements on dental pulp-derived cells (bDPCs), Bifix QM (BQM), Choice 2(C2), RelyX U200(RU200), Maxcem Elite(ME), and Multilink Automix(MA) were tested. The materials were incubated in DMEM for 72 h. A real-time cell analyzer was used to evaluate cell survival. The statistical analyses used were one-way ANOVA and Tukey-Kramer tests. BQM, RU200, and ME demonstrated a significant decrease in the bDPCs' index at 24 and 72 h (p≤0.001). These materials were found to be the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Recently, Arslan‐Malkoç et al () evaluated the cytotoxicity of different resin cements on dental pulp‐derived cells. Although different formulation has been used, RelyX U200 and Multilink Automix were cytotoxic to pulp cells and were capable of eliciting biological responses.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Arslan‐Malkoç et al () evaluated the cytotoxicity of different resin cements on dental pulp‐derived cells. Although different formulation has been used, RelyX U200 and Multilink Automix were cytotoxic to pulp cells and were capable of eliciting biological responses.…”
Section: Discussionmentioning
confidence: 99%
“…Rely X Veneer is composed of only two monomers: BisGMA and TEGDMA, whereas Variolink II and AllCem Veneer present an additional monomer type, UDMA and BisEMA, respectively. A current study has demonstrated that TEGDMA and BisGMA present severe cytotoxicity according to the following rank order: BisGMA>UDMA>TEGDMA>BisEMA 8 . Therefore, based on our previous results, it is possible to suggest that the presence of a third monomer in the veneer composition may decrease their cytotoxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that resin cements present toxic reaction in cell cultures by unreacted monomers released from the material during the polymerization reaction, which is related to thickness, light intensity, and photoactivation times of the material 8,12 . Is has also been demonstrated that comonomers, additives, and reaction products are released from polymerized cements 12,18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations